Rekonstruksi Jihad Menuju Peradaban Pengetahuan Masa Otoritas - Muhammad Raushan Kanzul Fikri (AL-Ikhtiar : Jurnal Studi Islam, 2026)
Jihad is an important requirement in Islamic teachings, obligatory for every Muslim, according to their individual abilities and capacities. However, in the development of religious discourse and public perception, the term jihad is often reduced to the meaning of war (qitāl). This narrowing of meaning has given rise to a negative stigma, namely the assumption that jihad is synonymous with violence and uncivilized acts. However, when referring to authoritative sources in Islam, both the Quran and the Hadith, jihad has a much broader and nobler meaning. Jihad encompasses spiritual struggle, patience, self-control, da'wah (preaching), devotion to parents, and a commitment to fighting for good in various aspects of life. One form of jihad emphasized in the Prophet's hadith is the pursuit of knowledge. The Prophet stated that those who go out to seek knowledge are on the path of Allah until they return. The interpretation of jihad as the pursuit and development of knowledge demonstrates that jihad is not merely a physical act, but an intellectual, moral, and spiritual process oriented towards the advancement of oneself and society. If this broad understanding is realized, the stigma that jihad is an uncivilized activity will naturally fall away. In fact, jihad in the form of knowledge has made a significant contribution to the advancement of knowledge and the development of civilization. From this framework of thought, the concept of "civilizational jihad" was born: jihad oriented toward the development of knowledge, intellectual advancement, the creation of a dignified social order, and the formation of a superior society. With this comprehensive understanding, jihad returns to its essence as a transformative force for a more civilized life. Abstrak Jihad merupakan tuntunan penting dalam ajaran Islam yang diwajibkan kepada setiap muslim sesuai kemampuan dan kapasitas masing-masing. Namun dalam perkembangan wacana keagamaan maupun persepsi publik, istilah jihad kerap direduksi hanya pada makna perang (qitāl). Penyempitan makna ini kemudian melahirkan stigma negatif, yaitu anggapan bahwa jihad identik dengan kekerasan dan tindakan tidak beradab. Padahal, jika merujuk pada sumber-sumber otoritatif dalam Islam, baik al-Qur’an maupun hadis, jihad memiliki cakupan makna yang jauh lebih luas dan lebih mulia. Jihad mencakup perjuangan spiritual, kesabaran, pengendalian hawa nafsu, dakwah, pengabdian kepada orang tua, hingga komitmen untuk memperjuangkan kebaikan dalam berbagai aspek kehidupan.Salah satu bentuk jihad yang ditegaskan dalam hadis Nabi adalah menuntut ilmu. Rasulullah menyebut bahwa orang yang keluar untuk mencari ilmu berada di jalan Allah hingga ia kembali. Pemaknaan jihad sebagai pencarian dan pengembangan ilmu ini menunjukkan bahwa jihad bukan hanya tindakan fisik, melainkan proses intelektual, moral, dan spiritual yang berorientasi pada kemajuan diri dan masyarakat. Jika pemahaman yang luas ini dihidupkan, stigma bahwa jihad adalah aktivitas yang tidak beradab akan gugur dengan sendirinya. Bahkan, jihad dalam bentuk ilmu memiliki kontribusi besar bagi kemajuan pengetahuan dan pembangunan peradaban. Dari kerangka pemikiran inilah lahir konsep “jihad peradaban,” yakni jihad yang berorientasi pada pengembangan ilmu, kemajuan intelektual, penciptaan tatanan sosial yang bermartabat, serta pembentukan masyarakat yang unggul. Dengan pemaknaan komprehensif ini, jihad kembali pada hakikatnya sebagai energi transformasi menuju kehidupan yang lebih beradab